Profile of Breast Cancer Patients with Radiotherapy in Hasan Sadikin Hospital Bandung - Atikah Larasati; Marhendra Satria Utama; Adji Kusumadjati (National Cancer Center - Dharmais Cancer Hospital, 2022)
Background: Breast cancer is the most common cancer in women worldwide and in Indonesia. Most patients arrived at the hospital too late to receive the optimal benefit from breast cancer therapies, in which radiotherapy is one of the essential modalities. Radiotherapy is conducted as a local control by using the principle of ionizing radiation to eradicate the growth of cancer cells, hence reducing the chances of recurrence and enhancing survival rates. Some of the side effects include skin conditions that can manifest as redness and dry skin, fatigue, lymphedema, and chest wall fibrosis. Data and research on the profile of breast cancer patients with radiotherapy were still limited in Indonesia, particularly in West Java. This study aimed to assess the profile of breast cancer patients in Hasan Sadikin Hospital Bandung.Methods: This study was conducted with the retrospective descriptive quantitative method. The sampling technique was total sampling using 280 medical records of breast cancer patients with radiotherapy from January 1, 2018, until December 31, 2019, which were registered in the Hospital-Based Cancer Registry at the Radiotherapy Department, Hasan Sadikin General Hospital.Results: Breast cancer patients undergoing radiotherapy were mostly in the 45–54 years age group (36.4%). The most common chief complaint was a lump in the breast (66.4%), particularly in the left breast (45.0%). About 22.5% of all patients arrived at a locally advanced stage and 30.7% at an advanced stage with bone metastasis (10.6%), histopathological subtype Invasive Carcinoma No Special Type (IC-NST) (81.1%), and molecular subtype luminal B (9.6%). The most widely performed therapies were total mastectomy surgery (16.1%), neoadjuvant chemotherapy (62.9%), and complete adjuvant radiotherapy (47.1%) with External Beam Radiotherapy (EBRT) method using LINAC (71.1%).Conclusions: Breast cancer is a health burden in Hasan Sadikin General Hospital and remains one of the national health priorities. Further evaluation of management and follow-up studies need to be done to improve the implementation of therapies for patients and reduce the incidence rate